PEMBELAJARAN BAHASA BERBASIS SOSIOKULTURAL - richa dwi rahmawati (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2019)
PEMBELAJARAN BAHASA BERBASIS SOSIOKULTURAL Richa Dwi Rahmawati Program Pascasarjana Magister PGMI UIN Sultan Syarif Kasim Riau Telp: 082288369248 E-Mail : richarahmawati28@gmail.com Abstract: Language is a communication tool, the connector between humans. Language learning emphasizes students’ communication skill. Language learning process is also affected by multi-cultures in Indonesia. The problem is being answered by library research. The data is taken from certain references; primary data, secondary data and also supporting data. The result shows that sociocultural language learning is a learning which integrates culture as a part of learning process. Multicultural education is emphasized in an attempt to empower and improve minority and cultural group representation in curriculum and textbook. Sociocultural education is a process of giving how to respect, be honest and tolerant towards multi-cultures in plural society life. Sociocultural factors that affect language learning are social interaction and acculturation Keywords: language, learning, sociocultural, multicultural education.